Systemanalys av skogsbränsletransporter - Engblom, Gabriel (2007)
At the end of 70s and the beginning of 80s, 18 terminals was built and used for chipping wood residue from clear cuttings. Most of the terminals was terminated before the 2000s but with the high oil- and energy prices that we can see today there might be a place for these terminals again. The goal with the study was to analyze and compare economical differences between 5 different logistical systems, collected data was used with a set of formulas. The systems include long range transport of slash, chips and bundles. Three of the systems include transport by lorry to industry the last two includes a terminal with access to train transport. At the terminal bundles will be unloaded from a lorry to a train or slash will be chipped directly on to a train and thereafter be transported to industry. The end product at the industry in all cases is chips and all the systems are being presented in SEK/ton and SEK/MWh.